Przegląd mierników stosowanych w zrównoważonych kartach wyników - Nieplowicz, Maria (Review of the Measures Applied in Balanced Scorecard, 2005)
This paper discusses performance measures in basic perspectives of the Balanced Scorecartl (financial, customer, internal proccess and learning and growth) and in specific perspectives of the Balanced Scorecard (competitor, cooperative, concern, organizational, communication, implementation, internet, supplier, innovation, institutional and public).
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (3); 2005; nr 1062, s. 330-338